Cell leakage mechanism and time-kill studies on Staphylococcus aureus after exposure to ethanol leaf extract of Muntingia calabura L. - Nanik Sulistyani; Nurkhasanah Mahfudh; Rizky H Mawardi; Zainul A Zakaria (University of Benin, 2023)
Purpose: To determine the effect of the ethanol leaf extract of M. calabura (EEMC) on cell leakage and time-kill against S. aureus. Methods: The leaves were macerated with 96 % ethanol (1:8; w/v) for 27 h to produce EEMC. Chemical compounds of EEMC were analyzed using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Various concentrations of EEMC (12.5; 25; 50; 100 mg/mL) were tested to determine the Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against S. aureus. Furthermore, EEMC was tested for its effect on cell leakage, changes in extracellular electrical conductivity, and time-kill against S. aureus. UV-spectrophotometer was used to test for leakages of nucleic acid, protein, DNA, and RNA, while atomic absorption spectrophotometer was used to evaluate leakage of potassium ion (K+ ). Results: The MIC and MBC of EEMC against S. aureus were 10 % w/v (100 mg/mL). The highest cell leakage occurred in S. aureus exposed to 2x MIC, with leakages of protein, DNA, RNA, and K+ reaching 137.79 ± 58.99, 2298 ± 263.26, 1839 ± 210.61 and 770.86 ± 40.11 µg/mL respectively. The EEMC (1x MBC and 1.5x MBC) killed S. aureus in 24 h. Analysis of LC-MS/MS of EEMC showed that flavonoids (48.33 %) followed by anthraquinones (16.10 %) were the major classes of compounds present in the extract. Conclusion: The ethanol leaf extract of M. calabura kills S. aureus by inducing cell leakage possibly due to flavonoids and anthraquinones contained in it. The extract should be further isolated and its active principles with potent antibacterial properties developed for therapeutic applications.